Impact of Age, Sex, and Renal Function on the Efficacy and Safety of Direct Oral Anticoagulants vs. Vitamin K Antagonists for the Treatment of Acute Venous Thromboembolism: A Meta-Analysis of 22,040 Patients - Zhou, Bo; Wu, Haoyu; Wang, Chen; Lou, Bowen; She, Jianqing (Frontiers in Cardiovascular Medicine, 2021)
Objective: In this study, we conducted a meta-analysis to assess the impact of age, sex, and renal function on the efficacy and safety of direct oral anticoagulants (DOACs) vs. vitamin K antagonists (VKAs) for the treatment of acute venous thromboembolism (VTE). Methods: Electronic databases (accessed till June 2021) were systematically searched to investigate randomized clinical trials evaluating apixaban, dabigatran, edoxaban, and rivaroxaban vs. VKAs for the treatment of acute VTE. Results were presented as odds ratio (OR) and 95% CIs. Results: Direct oral anticoagulants were associated with a borderline higher efficacy in women (OR: 0.79, 95% CI: 0.62–1.02), a significantly higher efficacy in patients with age more than 75 years (OR: 0.51, 95% CI: 0.32–0.80), and creatinine clearance <50 ml/min (OR: 0.57, 95% CI: 0.32–0.99). The primary safety endpoint of major or clinically relevant non-major bleeding was significantly reduced in DOACs as compared to VKAs in both patients with age <75 years (OR: 0.79, 95% CI: 0.70–0.89) and patients with age more than 75 years (OR: 0.75, 95% CI: 0.59–0.96). DOACs also show an advantage in terms of major or clinically relevant non-major bleeding in men (OR: 0.72, 95% CI: 0.60–0.86) and patients with creatinine clearance of more than 50 ml/min (OR: 0.75, 95% CI: 0.67–0.84). Conclusions: Direct oral anticoagulants have exhibited clinical preference among patients with acute VTE with decreased thrombosis and bleeding events, especially in patients with age more than 75 years and creatinine clearance <50 ml/min.